2011
DOI: 10.1371/journal.pone.0023937
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs in Patients with Chronic Hepatitis C and Non-Alcoholic Fatty Liver Disease

Abstract: MicroRNAs miR-122, miR-34a, miR-16 and miR-21 are commonly deregulated in liver fibrosis and hepatocellular carcinoma. This study examined whether circulating levels of these miRNAs correlate with hepatic histological disease severity in patients with chronic hepatitis C infection (CHC) or non-alcoholic fatty-liver disease (NAFLD) and can potentially serve as circulating markers for disease stage assessment. We first used an in vitro model of hepatitis C virus (HCV) infection to measure the extracellular level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
463
6
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 516 publications
(518 citation statements)
references
References 37 publications
45
463
6
4
Order By: Relevance
“…As a consequence the colonization and dissemination of HCC are also favored. Serum levels of this miRNA (Cermelli et al, 2011) are elevated in patients with chronic hepatitis C infection than in control individuals and these are related to the degree of fibrosis. Recently, Xu et al (2015) found that miR-34a induces cellular senescence through the negative modulation of telomere pathway in human HCC by targeting c-Myc and FoxM1 involved in the activation of telomerase reverse transcriptase (hTERT) transcription.…”
Section: Mir-34amentioning
confidence: 99%
“…As a consequence the colonization and dissemination of HCC are also favored. Serum levels of this miRNA (Cermelli et al, 2011) are elevated in patients with chronic hepatitis C infection than in control individuals and these are related to the degree of fibrosis. Recently, Xu et al (2015) found that miR-34a induces cellular senescence through the negative modulation of telomere pathway in human HCC by targeting c-Myc and FoxM1 involved in the activation of telomerase reverse transcriptase (hTERT) transcription.…”
Section: Mir-34amentioning
confidence: 99%
“…40,44,45 Serum/plasma levels of miR-122 correlate with hepatic necro-inflammation, liver damage, cell death and increased aminotransferase levels in acute and chronic liver diseases. 44,[46][47][48][49] Interestingly, hepatic and circulating miR-122 levels do not correlate in NAFLD 14,39,[50][51][52][53][54][55] or viral hepatitis 41,47,49,56 although both have been statistically associated with various measures of disease severity in these studies. Together these studies show that miR-122 may play a role in most liver diseases.…”
Section: Microrna-122mentioning
confidence: 62%
“…14 Together these studies suggest that differentially expressed miRs in humans and animal models of NASH regulate genes with diverse functions involved in the pathogenesis of NAFLD, including metabolism of lipid and glucose, regulation of the unfolded protein response, endoplasmic reticulum stress, oxidative stress, cellular differentiation, inflammation and apoptosis. 14,36 Notably, miR-34a has been shown to be up-regulated in both human serum 50,51 and liver in humans and animal models of NAFLD. 14,55,121,122 Two recent studies suggest two differing mechanisms for the involvement of miR-34a in NASH pathogenesis through down-regulation of SIRT-1; a) leading to AMP kinase dephosphorylation and subsequent decreased phosphorylation of HMGCoA, ultimately leading to cholesterol accumulation 121 ; b) increased acetylation of p53 causing activation of apoptosis.…”
Section: Non-alcoholic Fatty Liver Disease (Nafld)mentioning
confidence: 99%
“…no positive correlation was observed between miR-122 level and HCV [22,23]. It may be due to not strong correlation between miR-122 level and HCV RNA level or the different cell line.…”
Section: Discussionmentioning
confidence: 84%